If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 1m = 4m + 21 Reorder the terms: 12 + 1m = 21 + 4m Solving 12 + 1m = 21 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 12 + 1m + -4m = 21 + 4m + -4m Combine like terms: 1m + -4m = -3m 12 + -3m = 21 + 4m + -4m Combine like terms: 4m + -4m = 0 12 + -3m = 21 + 0 12 + -3m = 21 Add '-12' to each side of the equation. 12 + -12 + -3m = 21 + -12 Combine like terms: 12 + -12 = 0 0 + -3m = 21 + -12 -3m = 21 + -12 Combine like terms: 21 + -12 = 9 -3m = 9 Divide each side by '-3'. m = -3 Simplifying m = -3
| 6n^2+24n-3=-3 | | z^4-2iz^2+1=0 | | x^2+3x-7=-3 | | 14x^4-4x^3+28x^2-8x=0 | | 2yx^2-6x-3y=0 | | 3k^2+3k-60=0 | | y=4x^2-8x+2 | | 2.5b-5=.5b+1 | | 5p^2+40p+80=0 | | af^3+64a= | | 2*4x*3y-4x*y= | | -5/2=-x/3 | | 7x^2-49x+70=0 | | f(x+8)=x^2-8x+9 | | 6X+7=5X+2 | | n^2-8n+15=0 | | 8x-6y+20= | | .67x+.5=x^2 | | 4x^2-15=-7x | | y=x^2-2x-7 | | 1+3=5y+3 | | 15m^2-31m+10=0 | | 2t+8-1t=-3 | | 7-2(9-6)= | | x+4b=3a | | 3(2x+3)=8-5(2x-3) | | -x^2+4x+3= | | -3+4=-2x-19 | | 0.2-8=-2 | | 3x*x-6x+51=0 | | 20=7x-1 | | 200+45x=50+55x |